PENERAPAN PEMBELAJARAN KOOPERATIF TIPE THINK PAIR SHARE (TPS) DALAM MENINGKATKAN HASIL BELAJAR PKn DI KELAS X 1 SMA KORPRI BANJARMASIN - Adawiah, Rabiatul; Agus, Dian; Aslami, Faisah (Vidya Karya Jurnal Kependidikan, 2013)
The teaching and learning civic education in senior high school of SMA KORPRI Banjarmasin so far is based on speech method and the teacher dominates the classroom. This condition creates the low motivation of students in learning and finally it has the significant impact to the low studentsâ achievment. This research has the objective to increase the studentsâ activity and achievment by implimenting cooperative learning type Think Pair Share. The subject of this research is the students of X 1 SMA KORPRI Banjarmasin that consist of 33 students. The technique of collecting data is done by test, observation, questionare, and documentation. The research result shows that the implimentation of cooperative learning type Think Pair Share in teaching and learning civic education can increase the studentsâ activity and achievment of X 1 SMA KORPRI Banjarmasin.